2017
DOI: 10.18203/issn.2454-5929.ijohns20175608
|View full text |Cite
|
Sign up to set email alerts
|

Powered endoscopic inferior turbinoplasty: clinical study

Abstract: <p class="abstract"><strong>Background:</strong> <span lang="EN-IN">Nasal obstruction is a common complaint in ENT clinics and significantly affect the patient`s quality of life. Inferior turbinate hypertrophy is one of the common causes of nasal obstruction, surgical reduction of inferior turbinate is indicated in refractory cases not responding to conservative measures and the optimal surgical technique is controversial. The aim of the study was to evaluate the clinical outcomes of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Pre-operatively, nasal obstruction was moderate to severe in all patients, at the first post-operative week 18 patients (60.0%) had no obstruction, and 12 (40.0%) had mild obstruction, on the 1 st post-operative month 23 (76.7%) patients had no obstruction and 7 patients still had mild nasal obstruction while on the 3 rd post-operative month the total number of patients with no obstruction was 26 (86.7%) and only 4 patients remained with mild one. 9 Turbinate hypertrophy grades: The present results demonstrated that there was a significant improvement (p<0.001) in turbinate hypertrophy grades at different follow up periods post-operatively (at 2 nd week post-operative, 3 patients (7.5%) had grade I , 25 patients (62.5%) had grade II and 12 patients (30%) had grade III . However, after 1 month, 20 patients (50%) had grade I, 16 patients (40%) had grade II and 4 patients (10%) had grade III.…”
Section: Post-operative Follow-up (Outcomes)supporting
confidence: 48%
See 2 more Smart Citations
“…Pre-operatively, nasal obstruction was moderate to severe in all patients, at the first post-operative week 18 patients (60.0%) had no obstruction, and 12 (40.0%) had mild obstruction, on the 1 st post-operative month 23 (76.7%) patients had no obstruction and 7 patients still had mild nasal obstruction while on the 3 rd post-operative month the total number of patients with no obstruction was 26 (86.7%) and only 4 patients remained with mild one. 9 Turbinate hypertrophy grades: The present results demonstrated that there was a significant improvement (p<0.001) in turbinate hypertrophy grades at different follow up periods post-operatively (at 2 nd week post-operative, 3 patients (7.5%) had grade I , 25 patients (62.5%) had grade II and 12 patients (30%) had grade III . However, after 1 month, 20 patients (50%) had grade I, 16 patients (40%) had grade II and 4 patients (10%) had grade III.…”
Section: Post-operative Follow-up (Outcomes)supporting
confidence: 48%
“…They found that regarding the grading of turbinate hypertrophy, pre-operatively, 11 patients (36.7%) had grade 2 and the remaining 19 patients (63.3%) had grade 3 while none had grade 1, post-operatively all the patients had grade 1. This improvement was statistically significant 9.…”
mentioning
confidence: 76%
See 1 more Smart Citation